The Study of Strategies in Learning English and English Academic Achievement - Hayati, Noor; Usman, Usman (Institut Agama Islam Negeri (IAIN) Curup, 2021)
English language learning is not a new thing in Indonesia, many people want to learn English for various purposes. However, not all students can easily achieve their goals and follow the learning process. One of the factors is language learning strategy. This research aimed to investigate the students’ English language learning strategies and its correlation with the English academic achievement. Descriptive and correlational design, quantitative and qualitative methods were applied in this research. The students’ English scores on their study report (KHS) and SILL were used as the instrument. The samples of this research were fifty third year students majoring in English at IAIN Samarinda. Moreover, three students were chosen to participate in the semi structured interview. The data of the research were analyzed using descriptive and Pearson Product Moment correlation. The result showed that the most preferred strategy used by the students was social strategy There was a significant correlation between students’ English language learning strategies and English academic achievement (r=.436, p=.001<.05).